2022
DOI: 10.1093/cdn/nzac082
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Appearance and Status of Appetite Following a Single Meal of Red Meat or a Plant-Based Meat Analog: A Randomized Crossover Clinical Trial

Abstract: Background Red meat is a nutrient-dense food and a dietary staple. A new generation of plant-based meat analogs (PBMA) have been designed to mimic the experience of eating meat, but there is limited evidence about their digestive efficacy and nutritional quality. Objectives We compared the postprandial digestive response of a single meal containing meat commercially raised in New Zealand including lamb, on-farm pasture-raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…The results of the present study add to those previously reported that the digestion speed of whey protein is higher than that of plant-based proteins [ 18 , 19 , 23 , 48 , 73 , 74 , 76 ], even after adding fibre. However, as previously noted, others have shown similar findings regarding AA appearance when comparing plant and animal proteins matched for net protein content [ 17 ]. One of the factors that could explain the reduced postprandial aminoacidemia concentrations observed after the PPF meals is the greater sequestration of AA in splanchnic tissue [ 45 , 78 , 79 ], which is known to be higher for plant vs. animal proteins [ 45 , 78 , 79 ].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The results of the present study add to those previously reported that the digestion speed of whey protein is higher than that of plant-based proteins [ 18 , 19 , 23 , 48 , 73 , 74 , 76 ], even after adding fibre. However, as previously noted, others have shown similar findings regarding AA appearance when comparing plant and animal proteins matched for net protein content [ 17 ]. One of the factors that could explain the reduced postprandial aminoacidemia concentrations observed after the PPF meals is the greater sequestration of AA in splanchnic tissue [ 45 , 78 , 79 ], which is known to be higher for plant vs. animal proteins [ 45 , 78 , 79 ].…”
Section: Discussionsupporting
confidence: 68%
“…The lack of increase in their postprandial plasma concentrations would classify them as limiting. Methionine’s low postprandial availability was recently flagged after plant-based protein ingestion in young [ 74 ] and older adults [ 17 , 76 ], miniature pigs [ 69 ], and rainbow trout [ 85 ]. Accordingly, we paid particular attention to methionine in the PPF blend design, yet reduced bioavailability of methionine occurred despite this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations